Combinations of Plant Essential Oil Based Terpene Compounds as Larvicidal and Adulticidal Agent against Aedes aegypti (Diptera: Culicidae) - Sarma, Riju (Sci Rep, 2019)
Insecticidal plant-based compound(s)in combinations may show synergistic or antagonistic interactions against insect pest. Considering the rapid spread of the Aedes borne diseases and increasing resistance among Aedes population against conventional insecticides, twenty-eight combinations of plant essential oil-based terpene compounds were prepared and tested against larval and adult stages ofAedes aegypti. Initially five plant essential oils (EOs) were assessed for their larvicidal and adulticidal efficacy and two of their major compounds from each EO were identified from GC-MS results. Identified major compounds namely Diallyldisulfide, Diallyltrisulfide, Carvone, Limonene, Eugenol, Methyl Eugenol, Eucalyptol, Eudesmol and α-pinene were purchased and tested individually against A. aegypti. Binary combinations of these compounds were then prepared using sub-lethal doses, tested and their synergistic and antagonistic effects were determined. The best larvicidal compositions were obtained while Limonene was mixed with Diallyldisulfide and the best adulticidal composition was obtained while Carvone was mixed with Limonene. Commercially used synthetic larvicide “Temephos” and adulticide “Malathion” were tested individually and in binary combinations with the terpene compounds. The results revealed that the combination of Temephos and Diallyldisulfide and combination of Malathion and Eudesmol were the most effective combination. These effective combinations bear potential prospect to be used against Aedes aegypti.